2016
DOI: 10.1177/2158244016669548
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effects of Different Glossing Conditions on EFL Learners’ Vocabulary Recall

Abstract: This quasi-experimental study examined the effects of different glossing conditions on English as a foreign language (EFL) learners' vocabulary recall. To this end, five glossing conditions were adopted (i.e., inference-gloss-gloss, gloss-retrievalgloss, inference-gloss-retrieval-gloss, gloss-retrieval-gloss-retrieval, and full glossing). The participants were 140 MA students of Teaching English as a Foreign Language (TEFL). They were randomly assigned to one glossing condition to read an English reading passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Overall, gloss appears to promote better vocabulary gain, especially on form recognition, regardless of the participants' language proficiency. It is consistent with findings from past studies (e.g., Danesh & Farvardin, 2016;Duan, 2018;Jung, 2016;Ko, 2012;Watanabe, 1997), which showed that glossing has a positive impact on L2 vocabulary learning. Surprisingly, target words in the contextual clue and no clue conditions were retained better in the meaning recall, even though they were less recognised compared to target words in the gloss condition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, gloss appears to promote better vocabulary gain, especially on form recognition, regardless of the participants' language proficiency. It is consistent with findings from past studies (e.g., Danesh & Farvardin, 2016;Duan, 2018;Jung, 2016;Ko, 2012;Watanabe, 1997), which showed that glossing has a positive impact on L2 vocabulary learning. Surprisingly, target words in the contextual clue and no clue conditions were retained better in the meaning recall, even though they were less recognised compared to target words in the gloss condition.…”
Section: Discussionsupporting
confidence: 93%
“…A considerable number of past studies have shown that overall gloss has a positive effect on vocabulary learning compared to the no gloss condition (Danesh & Farvardin, 2016;Duan, 2018;Jung, 2016;Ko, 2012;Watanabe, 1997). However, the contradicting notion is that gloss might deprive a learner's mental effort for searching and inferring the meaning of the word, causing a less affirmative result in vocabulary learning (Huang & Lin, 2014).…”
Section: Input Enhancementmentioning
confidence: 99%
“…The research employed a design in which it was impossible to separate the effect of textual glosses from other treatment effects (e.g. Danesh & Farvardin, 2016; Huang & Lin, 2014).…”
Section: Methodsmentioning
confidence: 99%